Implementation of In-Hospital Postpartum Glucose Tolerance Testing for People with Gestational Diabetes - Ayala, Nina K.; Fain, Audra C.; Smith, Megan M.; Schlichting, Lauren E.; Hamel, Maureen S.; Werner, Erika F. (American Journal of Perinatology, 2024)
Objective We aimed to evaluate uptake of the glucose tolerance test performed during delivery hospitalization as part of routine clinical care.Study Design This is a retrospective cohort study of people with GDM at a tertiary center. We collected 9 months of postimplementation data after the in-hospital (“early”) glucose tolerance test was adopted as a routine screening option. Adherence was compared between those who elected early glucose tolerance testing versus those who deferred testing to the standard postpartum period. Bivariable statistics including demographics, care team, and postpartum testing/visit attendance were compared between those who received early testing and those who did not using chi-square, Fisher's exact, and t-tests.Results A total of 681 patients with GDM delivered during the study period. Of those who had an early glucose tolerance test ordered (n = 408), 340 (83.3%) completed the test. Among those who did not complete an early glucose tolerance test (ordered and not completed or never ordered), only 104/341 (30.5%) completed any postpartum glucose testing in the first 12 months of postpartum. There were significant differences in characteristics in terms of race/ethnicity, insurance, type of gestational diabetes (A1GDM vs. A2GDM), diabetes medications, obstetric care provider, and delivery mode. Among those who completed early testing, 43.7% of participants had impaired glucose metabolism and 6.5% had values concerning for overt diabetes mellitus. Among those who deferred testing to the standard 6- to 12-week period, 24.0% had impaired glucose metabolism and none had overt diabetes. Those who completed an early glucose tolerance test had a lower rate of postpartum visit attendance compared with those who deferred (75.6 vs. 91.5%, p < 0.01).Conclusion In this cohort, when the early glucose tolerance test is offered in clinical practice, adherence rates are higher than when the test is deferred until the postpartum visit.Key Points
Keywords: gestational diabetes; postpartum; dysglycemia; glucose tolerance testing; implementation